2006
DOI: 10.1029/2005jd006598
|View full text |Cite
|
Sign up to set email alerts
|

Biases in total precipitable water vapor climatologies from Atmospheric Infrared Sounder and Advanced Microwave Scanning Radiometer

Abstract: [1] We examine differences in total precipitable water vapor (PWV) from the Atmospheric Infrared Sounder (AIRS) and the Advanced Microwave Scanning Radiometer (AMSR-E) experiments sharing the Aqua spacecraft platform. Both systems provide estimates of PWV over water surfaces. We compare AIRS and AMSR-E PWV to constrain AIRS retrieval uncertainties as functions of AIRS retrieved infrared cloud fraction. PWV differences between the two instruments vary only weakly with infrared cloud fraction up to about 70%. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 36 publications
(64 reference statements)
5
108
0
Order By: Relevance
“…In a comparison with Vaisala operational radiosondes over sea/ocean, Fetzer et al (2003) showed biases from −4 to 4 % for AIRS water vapour retrievals of the ∼ 2 km layer between the surface and 500 hPa. Also over (identical) ocean scenes, observational biases generally less than 5 % in IWV were found by Fetzer et al (2006), who compared the IWV observations of AIRS and AMSR-E (Advanced Microwave Scanning Radiometer -EOS, on board Aqua). A validation over land of AIRS retrievals of IWVs (version 4) by measurements of more than 375 GPS receivers over the continental USA (from April to October 2004) is described in Rama Varma Raja et al (2008).…”
Section: Airsmentioning
confidence: 94%
“…In a comparison with Vaisala operational radiosondes over sea/ocean, Fetzer et al (2003) showed biases from −4 to 4 % for AIRS water vapour retrievals of the ∼ 2 km layer between the surface and 500 hPa. Also over (identical) ocean scenes, observational biases generally less than 5 % in IWV were found by Fetzer et al (2006), who compared the IWV observations of AIRS and AMSR-E (Advanced Microwave Scanning Radiometer -EOS, on board Aqua). A validation over land of AIRS retrievals of IWVs (version 4) by measurements of more than 375 GPS receivers over the continental USA (from April to October 2004) is described in Rama Varma Raja et al (2008).…”
Section: Airsmentioning
confidence: 94%
“…The Atmospheric Infrared Sounder (AIRS), on the NASA Aqua satellite, provides profiles of atmospheric temperature, water vapour, and a number of trace gas species including ozone, using a nadir cross-track scanning infrared instrument with a 15-km field of view (Fetzer et al, 2006). Here we use Version 5 (V005) of the AIRS standard level 2 ozone products (Olsen et al, 2007a, b), obtained from the Goddard Earth Sciences (GES) Data Information and Services Center (http://disc.sci.gsfc.nasa.gov/AIRS/ data-holdings/by-data-product/data products.shtml).…”
Section: Campaign Datamentioning
confidence: 99%
“…Global TPW can be derived from satellite visible, infrared, and microwave sensors (i.e., Wentz and Spencer, 1998;Fetzer et al, 2006;John and Soden, 2007;Fetzer et al, 2008;Noël et al, 2004). However, no single remote sensing technique is capable of completely fulfilling the needs for climate studies in terms of spatial and temporal coverage and accuracy.…”
mentioning
confidence: 99%